Vascular Cell Induction Culture System Using Arabidopsis Leaves (VISUAL) Reveals the Sequential Differentiation of Sieve Element-Like Cells - Kondo, Yuki; Nurani, Alif Meem; Saito, Chieko; Ichihashi, Yasunori; Saito, Masato; Yamazaki, Kyoko; Mitsuda, Nobutaka; Ohme-Takagi, Masaru; Fukuda, Hiroo (The Plant cell, 2016)
Cell differentiation is a complex process involving multiple steps, from initial cell fate specification to final differentiation. Procambial/cambial cells, which act as vascular stem cells, differentiate into both xylem and phloem cells during vascular development. Recent studies have identified regulatory cascades for xylem differentiation. However, the molecular mechanism underlying phloem differentiation is largely unexplored due to technical challenges. Here, we established an ectopic induction system for phloem differentiation named Vascular Cell Induction Culture System Using Arabidopsis Leaves (VISUAL). Our results verified similarities between VISUAL-induced Arabidopsis thaliana phloem cells and in vivo sieve elements. We performed network analysis using transcriptome data with VISUAL to dissect the processes underlying phloem differentiation, eventually identifying a factor involved in the regulation of the master transcription factor gene APL. Thus, our culture system opens up new avenues not only for genetic studies of phloem differentiation, but also for future investigations of multidirectional differentiation from vascular stem cells.